Perancangan coconut center dengan pendekatan biomimetika di Tembilahan - Roqim Azyan Kemas; Yohannes Firzal; Mira Dharma Susilawaty (ARTEKS : Jurnal Teknik Arsitektur, 2020)
Coconut center design with biomimetic approach in Tembilahan Tembilahan is known as the country of the coconut expanse of the world who has the industry made from coconut, both from shell, stem and even from coconut fiber. The potential of the industry made from coconut in Indragiri Hilir has not received a positive response from the society because of the intense competition with the production of other raw materials., whereas coconut is one of the highest potentials that can be utilized to improve the regional economy. To support the development of the coconut industry, a coconut center is needed to accommodate a variety of activities related to coconuts such as handicraft centers and coconut development. By using a primary method in the form of a survey, as well as various sources of literature as a secondary method. In the design of the coconut center architecture, this biomimetic Architecture theme approach will be used which uses nature as a model and reference in design ideas; it can strengthen the natural aspects of the design object that refers to the function of crafts, research, production, education, and recreation. © 2020 Kemas Roqim Azyan, Yohannes Firzal, Mira Dharma Susilawaty